2011
DOI: 10.1111/j.1468-2435.2010.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Displacement Triggered by Floods in the Mekong Delta

Abstract: The links between environmental change and migration is a theme which has caused much public debate. This debate is driven partially by the lack of empirical research on the linkages and relationship between environment and migration. This article offers a contribution to the limited literature which examines the ways in which migration is linked to environmental push factors. Initial research into the current dynamics of population displacement and migration linked to flooding in the upper reaches of the Viet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 15 publications
4
107
1
Order By: Relevance
“…The impacts of past floods in the Vietnamese Mekong Delta expose the rural population's lack of access to alternative livelihoods and difficulty in maintaining existing livelihoods. Household debts contribute to the pressure to migrate to urban areas (Dun 2011). Similarly, in and around the Tonle Sap Lake in Cambodia, the impacts of repeated floods have contributed to migration Keskinen et al 2010).…”
Section: The Mekong River Basin Water Resources and Climate Changementioning
confidence: 99%
“…The impacts of past floods in the Vietnamese Mekong Delta expose the rural population's lack of access to alternative livelihoods and difficulty in maintaining existing livelihoods. Household debts contribute to the pressure to migrate to urban areas (Dun 2011). Similarly, in and around the Tonle Sap Lake in Cambodia, the impacts of repeated floods have contributed to migration Keskinen et al 2010).…”
Section: The Mekong River Basin Water Resources and Climate Changementioning
confidence: 99%
“…Flooding also posed a risk to traditional livelihoods in rural areas [9,11,12,14,15,20]. Dun found that the disruption caused to rice farmers in Vietnam by repeated flooding resulted in the decision to migrate as there was no alternative livelihood [14].…”
Section: Economic Stressorsmentioning
confidence: 99%
“…Dun found that the disruption caused to rice farmers in Vietnam by repeated flooding resulted in the decision to migrate as there was no alternative livelihood [14]. In Vietnam seasonal migration often occurs as a means for flood affected families to boost their income [13,14].…”
Section: Economic Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For some people, mobility is an integral part of their livelihood, which allows them to increase, diversify or secure their incomes. Such traditional coping strategies are jeopardized by increased environmental pressure due to climate change [35,36]. As environmental disruptions would be exacerbated with a 4 • C+ temperature increase, mobility might become a less-viable coping strategy.…”
Section: Implications For a 4 • C+ Worldmentioning
confidence: 99%